Tree shrew as a new animal model for musculoskeletal disorders and aging - Xiaocui Wei; Honghao Li; Jingyang Qiu; Jianlin Jiao; Xiongtian Guo; Gaosheng Yin; Ping Yang; Yi Han; Qiongzhi Zhao; Hao Zeng; Zhi Rao; Xuefei Gao; et al. (Bone Research)
Abstract Intervertebral disc degeneration (IDD), osteoarthritis (OA), and osteoporosis (OP) are common musculoskeletal disorders (MSDs) with similar age-related risk factors, representing the leading causes of disability. However, successful therapeutic development and translation have been hampered by the lack of clinically-relevant animal models. In this study, we investigated the potential suitability of the tree shrew, a small mammal with a close genetic relationship to primates, as a new animal model for MSDs. Age-related spontaneous IDD in parallel with a gradual disappearance of notochordal cells were commonly observed in tree shrews upon skeletal maturity with no sex differences, while age-related osteoporotic changes including bone loss in the metaphyses were primarily presented in aged females, similar to observations in humans. Moreover, in the osteochondral defect model, tree shrew cartilage exhibited behavior similar to that of humans, characterized by a more restricted self-healing capacity compared to the rapid spontaneous healing of joint surfaces observed in rats. The induced OA model in tree shrews was highly efficient and reproducible, characterized by gradual deterioration of articular cartilage, recapitulating the human OA phenotype to some degree. Surgery-induced IDD models were successfully established in tree shrews, in which the lumbar spine instability model developed slow progressive disc degeneration with more similarity to the clinical state, whereas the needle puncture model led to the rapid development of IDD with more severe symptoms. Taken together, our findings pave the way for the development of the tree shrew as a new animal model for the study of MSDs and aging.